Body Waves Retrieved From Noise Cross‐Correlation Reveal Lower Mantle Scatterers Beneath the Northwest Pacific Subduction Zone. Issue 19 (6th October 2020) - Zhang, Limeng; Li, Juan; Wang, Tao; Yang, Fan; Chen, Qi‐Fu
Abstract: Seismological studies have revealed heterogeneities at scales of 10–1, 000 km in the lower mantle. For the first time, we demonstrate here that seismic interferometry of ambient noise can be used to detect faint scattered waves. We locate scattering structures at depths of 900–1, 000 km from P‐to‐P scattered wave signals in stacks of vertical cross‐correlograms from dense seismic arrays in northeast China. Independently, we show that this scattering structure produces S‐to‐P converted signals in the recordings of a deep earthquake. We constrain the thickness (H), the contrasts of the shear wave speed (δVs), and density (δρ) of the anomaly using 1‐D synthetics. Our modeling of both the reflected and converted signals indicates that H = 10–20 km, δVs = −7.2%, and δρ = 0.6%, which are similar to values reported previously and consistent with the interpretation that the scattering structure is a fragment of the basaltic oceanic crust associated with the subducted Izanagi plate. Plain Language Summary: Analysis of surface waves in ambient noise has been widely applied to image the structure of the crust and mantle. However, it is more difficult to extract the signals of body waves in the deep mantle from ambient noise. We explore signals by cross‐correlation using ground motion recordings from dense seismic arrays in northeast China. We identify a scattering signal at time 200 s. By analyzing and comparing the results of conversion waves generated by deep earthquakes, we confirm that this scattering signal represents a kind of body wave reflected by a small‐scale structure in the mid‐mantle at depths of 900–1, 000 km. The successful extraction of the weak body waves generated by scatterers in the lower mantle provides a potential method for the global detection of fine‐scale heterogeneities in the mantle, which will provide a better understanding of the composition and structure of the mantle, and the geodynamic processes in the deep earth. Key Points: Seismic interferometry is a promising technique for mapping small‐scale heterogeneities in the lower mantle far from subduction zones We locate scattering structures at depths of 900–1, 000 km from P‐to‐P scattered wave signals beneath northeast China Scatterers in the lower‐mantle that generate the observed SP and PP phases are probably associated with the mid‐ocean ridge basalt